SumaRT/Nap vs Naproxen Sodium in Treatment and Disease Modification of Migraine: A Pilot Study. Issue 1 (10th September 2013) - Cady, Roger; O'Carroll, Phillip; Dexter, Kent; Freitag, Fred; Shade, Candace L.
<x xml:space="preserve">Abstract</x> Objective This pilot study explored the potential for 2 recognized acute migraine medications, 85 mg of sumatriptan plus 500 mg of naproxen sodium in a combination tablet (SumaRT/Nap) and 500 mg of naproxen sodium, to treat and modify the disease progression of migraine. In other words, can these medications both abort an acute attack of migraine and reduce the number of future migraine attacks? Background Patients suffering with moderate to severe attacks of migraine desire acute treatment. As migraine frequency increases, so does the need for more frequent relief of acute attacks. This may lead to medication overuse and potentially medication overuse headache (MOH). Ideally, acute medication would have the ability to abort an attack of migraine and reduce the likelihood of future attacks. Study Design The primary endpoint of this study was a reduction in migraine headache days from baseline through month 3 of the study. Subjects were randomized 1:1 to treat 14 or fewer migraines per month with SumaRT/Nap (Group A) or naproxen sodium (Group B) for 3 months. Subjects in group A utilized SumaRT/Nap were encouraged, but not required, to treat migraine headache within 1 hour of onset of headache when the pain was mild. They could re‐treat if needed after 2 hours. Subjects in group B utilized the same treatment strategy with 500 mg of naproxen sodium. Tablets of study medication were identical for both groups. Subjects recorded headache days, migraine attacks, duration of attacks, treatment, and treatment results daily on paper diaries. Subjects took the Migraine Disability Assessment Test (MIDAS) at randomization and 3 months later at the end of study. Results Naproxen sodium was associated with a statistically significant reduction in migraine headache days at month 3 compared to baseline (P = .0002). SumaRT/Nap was also associated with a reduction of migraine headache days, but this decrease did not reach statistical significance (P = .2). In addition, subjects in the naproxen sodium group had a statistically significant reduction of migraine attacks in all 3 months of the study compared to baseline. A greater than 50% reduction in the number of migraine headache days at month 3 occurred in 43% (6/14) of subjects in group B compared to 17% (3/18) of subjects in group A. Consistent with large regulatory studies comparing the efficacy of SumaRT/Nap with naproxen sodium, SumaRT/Nap in this study was statistically superior to naproxen sodium at 2 hours in reducing headache severity during months 2 and 3. There was a reduction of acute medication used from baseline to month 3 and improvement in MIDAS scores for both groups. Conclusion Naproxen sodium, when used as a sole acute treatment early in attacks, appears to reduce the frequency of headache days and migraine attacks for a select number of subjects over a 3‐month period. SumaRT/Nap is more effective at 2‐hour headache reduction than naproxen sodium alone, but has less impact on reducing attack frequency or the number of headache days. Both treatments were well tolerated, and there was no convincing evidence that either medication led to MOH.